How The Rhinoceros Got His Skin - Daron Parton
Rudyard Kipling's brilliantly funny tale of How the Rhinoceros got his Skin has been perfectly captured by Daron Parton's quirky and colourful illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall young children aged 3+.